The Evolution of Communication Theory Over the Past 50 Years: An Analysis of the Multi-Edition Book "Theories of Human Communication" 1978 - 2021 - Prahastiwi Utari; Pramana Pramana (Ianna Journal of Interdisciplinary Studies)
Background: Academic textbooks are indispensable resources facilitating the organisation and dissemination of scholarly knowledge within a given field. The scientific ideas set forth and elucidated in academic textbooks will delineate the trajectory and direction of how these ideas will be employed and utilised by a range of users. Consequently, academic textbooks indirectly influence the evolution of scholarly thought.